Decrease the content of sulphur in coal and mineral through metalurgic processes for indusrial use - Aramburú Rojas, Vidal Sixto (2007)
The sample that is the object of this research work is a kind of bituminous coal, from the Mount Huáscar, province of Oyón, department of Lima. Provided by the Coal Mine Company. The mineralogical characterization of the sample coal, to show the presence of the following minerals: Graphite (grf) and Pyrite (py). The percentage distribution indicates graphite and 96,91% 3,09% pyrite, the particles are mostly free, accordingly modal analysis indicates that the degree of liberation of graphite and pyrite is 100%, that is counted all particles are free, as can be seen in the photos N.º 1, 2 ,3 and 4. Based on the characterization done it can be concluded that sulfur is in the pyrite, which is the polluter coal. Metallurgical tests were conducted preliminary gravity and flotation; being the outcome of the gravity is not satisfactory. The three tests metallurgical more representative of flotation process, concentrate obtained indicate that the low percentage of ash in 62,8% improves the percentage of fixed carbon in 19,2% and increases the calorific power at 12,2% compared with the original coal (head); this indicates that improves the quality of coal. As for the decrease in the percentage of sulphur the best test selected is No. 3, where low of 2,32% to 1,37%. Also more time milling notes that the particles of pyrite are already beginning to rise in concentrate.